Membrane Electrolysis Assisted Gas Fermentation for Enhanced Acetic Acid Production - Verbeeck, Kristof; Gildemyn, Sylvia; Rabaey, Korneel (Frontiers in Energy Research, 2018)
Gas fermentation has rapidly emerged as a commercial technology for the production of low-carbon fuels and chemicals from (industrial) CO and/or CO2-rich feedstock gas. Recent advances in using CO2 and H2 for acetic acid production demonstrated that high productivity and substrate utilization are achievable. However, the costly constant addition of base and the energy-intensive nature of conventional recovery options (e.g. distillation) need to be overcome to drive organic acid production forward. Recently, membrane electrolysis has been presented as a technology that enables for the direct extraction of carboxylates across an anion exchange membrane into a clean and low pH concentrate stream. Continuous in-situ extraction of acetate directly from the catholyte of a microbial electrosynthesis reactor showed that membrane electrolysis allows pure product recovery while improving productivity. Here we demonstrate that the system can be further enhanced through additional input of electrolytic hydrogen, produced at higher energetic efficiency while improving the overall extraction efficiency. A gas-lift reactor was used to investigate the hydrogen uptake efficiency at high hydrogen loading rates. During stable operation acetate transport across the membrane accounted for 31% of the charge balancing, indicating that the use of external H2 can lead to a more efficient use of the extraction across the membrane. By coupling membrane electrolysis with the gas fermentation reactor the pH decrease associated with H2/CO2 fermentations could be prevented, resulting in a stable and zero-chemical input process (except for the CO2). This now enables us to produce more than 0.6 M of acetic acid, a more attractive starting point towards further processing.